USE AND DISPOSAL OF ACIDIC WATER CONDENSATE FROM GAS-FIRED BOILER UNITS: Array - Fialko, N.; Navrodska, R.; Gnedash, G.; Novakivskii, M.; Sbrodova, G. (Municipal economy of cities. Series: «Economy science», 2021)
During operation in boiler units of modern condensing boilers or modernization of old-style boilers, water condensate is formed due to heat-recovery equipment in the mode of cooling exhaust-gases below the dew point of water vapor. At natural gas is burned in equipment, the range of values of the pH value of the condensate is within the range of 3 ÷ 6. In this connection, the problem arises of the useful use of this condensate or its safe drainage into the sewer network. At useful use, the resulting condensate can be used for the needs of the boiler units (for washing boilers, in chemical water-purification systems) or outside the boiler house (for laundries, greenhouses, swimming pools, etc.). In the case of condensate drainage into the city sewer network, as a rule, its preliminary decarbonization is required. This is a necessary environmental measure and operational standard to protect the sewer network and related equipment, including treatment facilities, from premature wear. Among the directions of condensate decarbonization known in Ukraine, the most common are: - decarbonization by degassing by the contact method, which consists in removing CO2 from the heated solution by blowing air in the nozzle layer (ceramic or plastic), through which condensate flows. Degassing occurs due to the instability of the H2CO3 compound, which, when heated, easily decomposes into H2O and CO2; - chemical decarbonization, by combining carbon dioxide in an insoluble compound with various reagents, which are added to the container using a dispenser; - decarbonization by passing the condensate through a granular filter containing calcium carbonate, such as marble chips or lime. Removal of carbonic acid from condensate during filtration in a layer of marble chips is seen as the simplest method of decarbonization of water condensate from those considered. On the basis of this method of decarbonization, the authors propose a technical solution for the developed neutralizer with a description of its design and operating principle. The paper presents the results of calculated studies of the volumes of formed condensate and an example of its safe use in the case of modernization of a gas-fired water-heating boiler with a nominal thermal power of 1 MW by a heat-recovery system with simple or complex use of heat. It is shown that when using modern heat-recovery technologies in gas-fired boiler houses, there are different circuit and technical solutions for possible useful use or safe evacuation of acidic condensate formed during the implementation of these technologies. In cases where it is advisable to neutralize this condensate, there are effective methods for its decarbonization and appropriate equipment.